HUBUNGAN VARIABEL PEMBENTUK MINAT BERPERILAKU MENGGUNAKAN PENGUNGKAPAN INFORMASI NON-FINANSIAL UNTUK KEPUTUSAN INVESTASI PADA SEKURITAS Studi Pada Wakil Penjamin Emisi Efek - Wignojohartojo, Parwoto (JURNAL BISNIS STRATEGI, 2001)
This study was conducted to measure the causal relationship among components building the intention of financial analyst working as an underwriter in using nonfinancial information disclosure as additional information on financial statements to make investment decision on securities.Survey research was applied. Questionares were used to measure and collect data. The classical path analysis was employed. The result of the study shows that subjective norm has positive effect toward attitude and attitude has positive effect toward intention of financial analyst working as an underwriter in using nonfinancial information insignificant causal relationships between belief and attitude, between normative belief and subjective norm, between subjective norm and intention.